Yarning About Yarning as a Legitimate Method in Indigenous Research - Bessarab, Dawn; Ng'andu, B. (Indigenous Studies Research Network, 2010)
This article demonstrates the credibility and rigor of yarning, an Indigenous cultural form of conversation, through its use as a data gathering tool with two different Indigenous groups, one in Australia and the second in Botswana. Yarning was employed not only to collect information during the research interview but to establish a relationship with Indigenous participants prior to gathering their stories through storytelling, also known as narrative. In exploring the concept of yarning in research, this article discusses the different types of yarning that emerged during the research project, how these differences were identified and their applicability in the research process. The influence of gender during the interview is also included in the discussion.